Development of Google Sites-Based E-learning Using the Problem-Based Learning Model to Improve Student Learning Outcomes in Chemical Equilibrium Material - Ayu Anisa Larasati; Agung Tri Prasetya; Nuni Widiarti (Chemistry in Education, 2026)
This study aims to develop an e-learning platform based on Google Sites that is integrated with the Problem-Based Learning (PBL) model to improve student learning outcomes on the topic of chemical equilibrium.. Research instruments include expert validation sheets, student response questionnaires, and learning achievement tests conducted through pretest and posttest. The validation results showed that the developed media obtained scores of 85.3% from material experts and 86% from media experts, both categorized as very valid. Student response to e-learning media is also very practical, with a percentage of 88.7%. The effectiveness of the media was shown by a significant increase in learning outcomes, with an N-gain score of 0.72 categorized as high. Therefore, Google Sites–based e-learning integrated with the PBL model is considered valid, practical, and effective, making it feasible to use as an alternative learning medium for teaching chemical equilibrium material.